Corporate srategic planning of Asia Pacific Property Estates - Sarte, Cyrene Thistle C. (Animo Repository, 2015)
Asia Pacific Property Estates is a real estate brokerage company that started in 1997. It was started by 2 sisters who were real estate brokers and held their office at home. The brokers catered to corporate accounts looking for housing their expatriates. As the clientele increased and the company became recognized in the industry they hired staff and upgraded their office. The company now holds office in the Makati Central Business District, and consists of a total of 11 employees. It now has grown into a bigger organization with a complete line of professional pre- and post-sales services. Thus, the Company's workforce does not stop at simply sourcing properties for clients but includes personalized services which strive to suit and satisfy the entire range of requirements of its rapidly expanding client base.